Synthesis, Absorption Properties and Biological Evaluation of Some Novel Disazo Dyes Derived from Pyrazole Derivatives - Sener, Nesrin; Sener, Izzet; Yavuz, Serkan; Karci, Fikret (Asian Journal of Chemistry, 2015)
In this study, 20 novel disazo dyes containing pyrazole derivatives were synthesized by a convenient method. Diazotized aniline and some aniline derivatives were reacted with malononitrile to give 2-arylazomalononitrile derivatives 1(a-e). The synthesized 2-arylazomalononitrile derivatives were reacted with hydrazine and phenyl hydrazine to afford the corresponding 3,5-diamino-4-arylazo-1H-pyrazole 2(a-e) and 3,5-diamino-4-arylazo-1-phenylpyrazole 3(a-e). Diazotized compounds of 2(a-e)and 3(a-e) reacted with ethylacetoacetate to give 4-arylazo-3-amino-1H-pyrazole-5-ylazo-ethylacetoacetate 4(a-e) and 4-arylazo-3-amino-1-phenylpyrazole-5-ylazo-ethylacetoacetate 7(a-e). The obtained 4(a-e) and 7(a-e) were reacted with hydrazine and phenyl hydrazine to give disazo dyes 5(a-e), 6(a-e), 8(a-e) and 9(a-e), respectively. The synthesized disazo dyes were characterized by spectroscopic techniques as well as elemental analysis. The solvatochromic behaviours of these dyes in various solvents were examined. Acid-base effects on the absorption maxima of the dyes were also reported. Antimicrobial activities of the synthesized novel disazo dyes were investigated.